Gene-specific recruitment of positive and negative elongation factors during stimulated transcription of the MKP-1 gene in neuroendocrine cells - Fujita, Toshitsugu (Oxford University Press, 2007)
MAP kinase phosphatase-1 (MKP-1) controls nuclear MAP kinase activity with important consequences on cell growth or apoptosis. MKP-1 transcription is initiated constitutively but elongation is blocked within exon 1. It is unclear how induction of MKP-1 is controlled. Here, we report that the transcriptional elongation factors P-TEFb, DSIF and NELF regulate MKP-1 transcription in the pituitary GH4C1 cell line. Prior to stimulation, DSIF, NELF and RNA polymerase II (pol II) associate with the promoter-proximal region of the MKP-1 gene upstream of the elongation block site. Thyrotropin-releasing hormone (TRH) leads to recruitment of P-TEFb along the whole gene and a marked increase of DSIF and pol II downstream of the elongation block site, whereas NELF remains confined to the promoter-proximal region. 5,6-Dichloro-1-β-d-ribofuranosylbenzimidazole (DRB) an inhibitor of P-TEFb eliminated TRH stimulation of MKP-1 transcription. DRB specifically inhibited TRH-induced recruitment of DSIF and P-TEFb to the MKP-1 gene. Furthermore, DRB treatment eliminated TRH-induced progression along the MKP-1 gene of pol II phosphorylated on Ser-2 of its CTD. These results indicate that P-TEFb is essential for gene-specific stimulated transcriptional elongation in mammalian cells via mechanisms which involve the activation of the DSIF–NELF complex and Ser-2 phosphorylation of pol II.